Encapsulating bacteria in alginate-based electrospun nanofibers. (13th April 2021) - Diep, Emily; Schiffman, Jessica D.
Abstract : We developed GRAS nanofibers for the delivery of viable bacteria into the gut. Model bacterium were encapsulated in alginate-based nanofibers via electrospinning and a bacteria loading of 2.74 × 10 5 CFU g −1 of mat was achieved. Abstract : Encapsulation technologies are imperative for the safe delivery of live bacteria into the gut where they regulate bodily functions and human health. In this study, we develop alginate-based nanofibers that could potentially serve as a biocompatible, edible probiotic delivery system. By systematically exploring the ratio of three components, the biopolymer alginate (SA), the carrier polymer poly(ethylene oxide) (PEO), and the FDA approved surfactant polysorbate 80 (PS80), the surface tension and conductivity of the precursor solutions were optimized to electrospin bead-free fibers with an average diameter of 167 ± 23 nm. Next, the optimized precursor solution (2.8/1.2/3 wt% of SA/PEO/PS80) was loaded with Escherichia coli ( E. coli, 10 8 CFU mL −1 ), which served as our model bacterium. We determined that the bacteria in the precursor solution remained viable after passing through a typical electric field (∼1 kV cm −1 ) employed during electrospinning. This is because the microbes are pulled into a sink-like flow, which encapsulates them into the polymer nanofibers. Upon electrospinning the E. coli -loaded solutions, beads that were much smaller than the size of an E. coli were initially observed. To compensate for the addition of bacteria, the SA/PEO/PS80 weight ratio was reoptimized to be 2.5/1.5/3. Smooth fibers with bulges around the live microbes were formed, as confirmed using fluorescence and scanning electron microscopy. By dissolving and plating the nanofibers, we found that 2.74 × 10 5 CFU g −1 of live E. coli cells were contained within the alginate-based fibers. This work demonstrates the use of electrospinning to encapsulate live bacteria in alginate-based nanofibers for the potential delivery of probiotics to the gut.